Human Security and Coastal Diplomacy: A Comparative Study of Indonesia and Australia in Managing Tourist Safety - Fiya Ainur Rohmatika; Joko Sutopo (Westscience Press, 2026)
Coastal tourism safety presents a diplomatic human security agenda, especially for Indonesia as an archipelagic country (≈99,093 km of coastline) and Australia with its mature coastal safety regime. This study aims to assess how the principle of human security is translated into tourism safety governance and how Indonesia-Australia coastal diplomacy produces soft power. The methods used are comparative studies based on policy and document analysis (BPS; BPS-DIY; National Coastal Safety Report 2024; Plan of Action 2025–2029), descriptive statistics of visits, and institutional assessments. The results show a strong recovery in Indonesian tourist arrivals: 4.05 million (2020), 1.56 million (2021), 5.89 million (2022), 11.68 million (2023), and 13.90 million (2024). At the regional level, DIY recorded 9,699 foreign tourists in May 2025 (up 35.94% m/m), with a cumulative total of 32,823 visits from January to May, while domestic tourist movements reached 3,547,415 trips. In Australia, the Surf Life Saving network comprises ≈316 clubs with >198,000 members, 558 patrol services, and 8,857 rescues in 2023/24; epidemiological literature estimates a backwash-related mortality rate of ≈0.11 per million visits. Comparisons indicate a gap in the degree of institutionalization: Australia displays consistent standards, proficiency tests, and exposure-based reporting, while Indonesia still varies between regions. In conclusion, coastal tourism safety is a manifestation of human security which, through coastal diplomacy, generates reputational gains (soft power). Recommendations include establishing national beach SOPs, exposure-based reporting, consistent certification, and multilingual risk communication as prerequisites for integrating human security into tourism governance